Психолінгвістичний експеримент як метод дослідження природної категорії - Котис, Олена; Kotys, Olena (Lesya Ukrainka Eastern European National University, 2014)
У статті викладено методику проведення та результати психолінгвістичного експерименту, скерованого на виявлення вмісту, структури та прототипів категорії «музичні інструменти» в концептосфері носіїв польської лінгвокультури. Експеримент складався з трьох частин. При побудові експерименту ми виходили з того, що при збереженні образу музичних інструментів людина використовує різні способи кодування інформації (аудіальний, візуальний та вербальний). Відповідно, наш експеримент був зорієнтований на всі три форми фіксації інформації про музичні інструменти. Перший блок передбачав виявлення вербальної інформації, другий − візуальної та вербальної, третій − аудіальної та вербальної. Респондентами стали 77 польських студентів немузичних спеціальностей, які навчаються в Університеті Марії Склодовської-Кюрі (м. Люблін). Ми виявили, що ядро категорії складають гітара, скрипка та фортепіано, а на ближній периферії знаходяться орган, флейта і бубон. The article presents methodology and results of a psycholinguistic experiment. The experiment was conducted with the purpose to figure out the meanings, structure and prototypes of the category «musical instruments» in the conceptosphere of ordinary speakers of Polish language. The experiment consists of three parts. When designing the experiment we considered that when preserving the cognitive image of musical instruments humans use different ways of encoding information (audial, visual and verbal). Respectively, our experiment was directed onto the three abovementioned forms of fixation of information about musical instruments. The first part of the experiment was directed onto investigation of the verbal information, the second – onto visual and verbal and the third part was designed to find out about audial and verbal information that is connected with the images of musical instruments. There were 77 respondents, none of them studying music as their major; all the participants are the students of Maria Curie-Skłodowska University, Lublin, Poland. The investigation shows that the nucleus of the category is made up by guitar, violin and piano, whilst organ, flute and tambourine are included into close periphery.
Psycholinguistic Experiment as a Method of Investigating a Natural Category
Keywords: психолінгвістичний експеримент; категорія; ядро; прототип; периферія; psycholinguistic experiment; category; nucleus; prototype; periphery